Hilaire Belloc: Del Estado del bienestar al Estado servil - Vera, Alfonso Díaz Vera (REVISTA PROCESOS DE MERCADO, 2017)
Hilaire Belloc (1870-1953) criticized the social legislation passed by the British Liberal Party before the Great War, which represented the emer-gence of the modern Welfare State. His criticism was based on the ideas of a school of thought called distributism. Based upon the principles of Catholic Social Teaching, especially the encyclical Rerum novarum. This Thomist rooted school of thought praised that the means of production should be spread as widely as possible. Belloc believed that attempts of social reform by state inter-vention, dissociated from fundamental principles, would lead to results oppo-site to those initially intended. Social reforms aimed to improve the status of workers could lead, by the needs of their sustainability, to an economy in which certain people would be forced by regulation to work for others or for the state, who likewise would have to take care of them. Belloc coined the concept “Ser-vile State” for this kind of society. Keywords: Hilaire Belloc; Welfare State; Servile State; collectivism JEL codes: B14, B15, B25 Resumen: Hilaire Belloc (1870-1953) criticó la legislación social del Partido Li-beral en la Inglaterra de los años anteriores a la Primera Guerra Mundial, considerada precedente del Estado del Bienestar. Su crítica se basó en una lí-nea de pensamiento conocida como distributismo, que, fundamentándose en una filosofía de raíz tomista y tomando como punto de partida la encíclica Rerum Novarum, defendía la distribución más amplia posible de la propiedad de los medios de producción. Para Belloc los intentos de reformar la sociedad mediante la intervención estatal, disociados de principios fundamentales y en-raizados en una filosofía errónea, no consiguen sino acrecentar los problemas que tratan de resolver. De este modo, el reformador que emplea sus herramien-tas de planificación en aras de la mejora social acaba promoviendo la impo-sición de diversas formas de trabajo obligatorio, características del tipo de relaciones sociales que Belloc definió como Estado Servil. Palabras clave: Hilaire Belloc; Estado del Bienestar; Estado Servil; colectivismo. Clasificación JEL: B14, B15, B25